Supplemental Pay for Cash Collateral of Police Officers during Quarantine: Administrative Discretion of Authorized Officials on Deciding about Its Payment (Law and Safety, 2021)
The author has researched the norms of positive law, which contain instructions on the establishment and payment of supplemental pay to the cash collateral during quarantine for police officers. A comprehensive, complete and objective study of legal basis for the supplemental pay to the cash collateral of police officers during quarantine is impossible without understanding the law enforcement practices and interpretation used by authorized officials when deciding whether or not to make the supplemental pay to the cash collateral of police officers. The normatively determined grounds for the supplemental pay and the actual substantiation of the application of such payments for police officers have been analyzed. Objectivity and completeness are impossible without analyzing all the arguments, including those voiced by the representatives of the administration of the territorial agencies of the National Police, as legal entities of public law. It has been emphasized that the administrative discretion of authorized officials should embody the principles of the rule of law, respect for human rights and freedoms, and should not pursue the realization of economic private interests, including the interests of subjects of authoritative powers. Restrictions on the application of the supplemental pay to the cash collateral of police officers during quarantine are the direct restriction of the social rights of representatives of a particular profession – police officers. The legal position for protecting the social right of police officers for the supplemental pay, as well as the affiliation of this right to each police officer has been defended.At the same time, the legal position on the need for the supplemental pay for all police officers has been additionally substantiated, based on the tasks facing the National Police and the provision of police services to the population.The author has argued the legal position of the completeness of social rights of police officers during quarantine, which are impossible without appropriate the supplemental pay to the cash collateral of police officers during quarantine.
Keywords: quarantine; police force; supplemental pay; cash collateral; police services; law and order; public safety.